A human neutralizing antibody targets the receptor-binding site of SARS-CoV-2 - Shi, Rui; Shan, Chao; Duan, Xiaomin; Chen, Zhihai; Liu, Peipei; Song, Jinwen; Song, Tao; Bi, Xiaoshan; Han, Chao; Wu, Lianao; Gao, Ge; Hu, Xue; et al. (Nature (London), 2020)
An outbreak of coronavirus disease 2019 (COVID-19) 1 – 3 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 4 , has spread globally. Countermeasures are needed to treat and prevent further dissemination of the virus. Here we report the isolation of two specific human monoclonal antibodies (termed CA1 and CB6) from a patient convalescing from COVID-19. CA1 and CB6 demonstrated potent SARS-CoV-2-specific neutralization activity in vitro. In addition, CB6 inhibited infection with SARS-CoV-2 in rhesus monkeys in both prophylactic and treatment settings. We also performed structural studies, which revealed that CB6 recognizes an epitope that overlaps with angiotensin-converting enzyme 2 (ACE2)-binding sites in the SARS-CoV-2 receptor-binding domain, and thereby interferes with virus–receptor interactions by both steric hindrance and direct competition for interface residues. Our results suggest that CB6 deserves further study as a candidate for translation to the clinic. Two monoclonal antibodies isolated from a patient with COVID-19 are shown to interfere with SARS-CoV-2–receptor binding, and one displays potent action against this virus in vitro and in a rhesus macaque model.